2020
DOI: 10.1177/0300060519895353
|View full text |Cite
|
Sign up to set email alerts
|

Saturated hydrogen alleviates CCl4-induced acute kidney injury via JAK2/STAT3/p65 signaling

Abstract: This study assessed the protective effects of saturated hydrogen against CCl 4-induced acute kidney injury (AKI) in mice, and investigated signaling pathways activated by exposure to saturated hydrogen. Methods: A mouse model of CCl 4-induced AKI was established; some mice were treated with saturated hydrogen. Levels of cystatin C and kidney injury molecule 1 were determined using enzyme-linked immunosorbent assays. Blood urea nitrogen and serum creatinine were measured on a fully automated biochemical analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Zhu et al (Zhu et al, 2020)reported that curcumin alleviated septic AKI via inhibiting JAK2/STAT3 signaling pathway. Wu and his colleagues revealed that saturated hydrogen attenuated AKI by repressing JAK2/STAT3 signaling pathway (Wu et al, 2020). Moreover, diosmetin relieved AKI through enhancing Nrf2/HO‐1 signaling pathway (Wang, Zhang, et al, 2020), sirtuin 5 reduced AKI by promoting Nrf2/HO‐1 signaling pathway (Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al (Zhu et al, 2020)reported that curcumin alleviated septic AKI via inhibiting JAK2/STAT3 signaling pathway. Wu and his colleagues revealed that saturated hydrogen attenuated AKI by repressing JAK2/STAT3 signaling pathway (Wu et al, 2020). Moreover, diosmetin relieved AKI through enhancing Nrf2/HO‐1 signaling pathway (Wang, Zhang, et al, 2020), sirtuin 5 reduced AKI by promoting Nrf2/HO‐1 signaling pathway (Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…HRS markedly reduced interstitial congestion, edema, and hemorrhage in renal tissue, prevented renal injury, and promoted renal function recovery after I/R injury in rats through antiapoptotic and anti-inflammatory actions in kidney cells [ 146 ]. Other authors described that HW significantly reduced the increased postvoid residual volume in obstructed rats and ameliorated bladder dysfunction secondary to bladder outlet obstruction by attenuating oxidative stress [ 147 ].…”
Section: Preventive and Therapeutic Applications Of H 2 mentioning
confidence: 99%
“…In addition, histological studies on the kidney of CCL 4 -treated mice were similar with other studies. [ 51 52 53 ]…”
Section: Discussionmentioning
confidence: 99%